Molecular characterization of native potato (Solanum spp.) Chungui, Ayacucho, using AFLP - Gonzales Mamani, Juan C. (2014)
Genetic diversity of 25 morphotypes of native potatoes Solanum spp. from Chungui (La Mar, Ayacucho) were assess. Morphotypes collected were micropropagated in Murashigue Skoog medium (1962). DNA extraction proceeded using the CTAB method modified from 3 weeks leaves crop, good quality and quantity of DNA was able to use the AFLP. Enzymatic digestion of the DNA was performed using EcoRI and MseI. Three combinations of AFLP primers with three selective nucleotides were used, resulting in a total of 85 clearly discernable bands, of which 63 were polymorphic. The combination E37 – M50 showed the most informative polymorphic index content of 0.43. The presence/absence of polymorphic bands was evaluated using the Simple Matching coefficient similarity and clustering analysis using the UPGMA. The dendrogram produced had a cophenetic correlation coefficient r= 0.7. At the level 0.64 of Simple Matching coefficient similarity, the dendrogram grouped the morphotypes of native potatoes in 4 genetic groups, it not found duplicated morphotypes, despite having some morphotypes very similar. Our results would be showing the highly informative power of AFLP markers for the analysis of genetic diversity of native potatoes.